A newly developed porcine training model for transurethral piecemeal and en bloc resection of bladder tumour - Teoh, Jeremy Yuen Chun; Cho, Chak Lam; Wei, Yong; Isotani, Shuji; Tiong, Ho Yee; Ong, Teng Aik; Kijvikai, Kittinut; Chu, Peggy Sau Kwan; Chan, Eddie Shu Yin; Ng, Chi Fai (Springer, 2019)
Purpose: The Asian Urological Surgery Training & Education Group (AUSTEG) has been established to provide training and education to young urologists in Asia. We developed and validated a porcine bladder training model for transurethral resection of bladder tumour (TURBT). Methods: Urology residents and specialists were invited to test the training model. They were asked to complete a pre-task questionnaire, to perform piecemeal and en bloc resection of ‘bladder tumours’ within the training model, and to complete a post-task questionnaire afterwards. Their performances were assessed by faculty members of the AUSTEG. For the face validity, a pre-task questionnaire consisting of six statements on TURBT and the training model were set. For the content validity, a post-task questionnaire consisting of 14 items on the details of the training model were set. For the construct validity, a Global Rating Scale was used to assess the participants’ performances. The participants were stratified into two groups (junior surgeons and senior surgeons groups) according to their duration of urology training. Results: For the pre-task questionnaire, a mean score of ≥ 4.0 out of 5.0 was achieved in 5 out of 6 statements. For the post-task questionnaire, a mean score of ≥ 4.5 out of 5.0 was achieved in every item. For the Global Rating Scale, the senior surgeons group had higher scores than the junior surgeons group in 8 out of 11 items as well as the total score. Conclusion: A porcine TURBT training model has been developed, and its face, content and construct validity has been established. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.